Early diagnosis of oral cavity carcinomas: The best prognostic factor - Edgard NEHMÉ; Chadi FARAH; Jeanine HOYEK-GEBEILY; Hachimia FAHS; Alexandre SABER; Antoine MELKANE (International Arab Journal of Dentistry (IAJD), 2017)
Oral mucosa neoplasms are most often pre-malignant lesions that evolved in squamous cell carcinoma (90% of cancers of the oral cavity). Tobacco and alcohol are the two most incriminated etiological factors. Other etiologies have also been mentioned, in particular the oncogenicity of certain viruses like the human papillomavirus(HPV). However, other types of cancer may occur mainly in young adults whose starting point is generally a salivary gland (10% of cancers of the oral cavity). From two clinical cases, squamous cell carcinoma and mucoepidermoid carcinoma, we describe the etiopathogenesis and the clinical characteristics as well as the histopathological particularities, diagnosis and prognosis of each of these entities. We also developped the interest of an early detection of the lesions that will provide the patient a better prognosis even though the therapeutic strategy is established in the best conditions